Effect of distractions due to the use of the cell phone while driving - Tábora Cruz, Olver Alexander (2025)
Distracted driving is one of the most important human factors in transportation safety and it is, therefore, a risk that is becoming a growing concern for road safety. Research establishes that cell phone use may be the most important source of distraction for drivers inside the vehicle since its use adds cognitive, physical, or visual demands on the driver towards a secondary task that diverts attention from critical activities for a safe driving, and then, can adversely affect driver behavior and performance. The objective of this research was to study the effects of distractions due to cell phone use on the driver's responses during the driving task and its link with the occurrence of traffic accidents. The results suggest that cell phone use, regardless of the tasks and modality used, has a negative effect on the behavior and performance of drivers and, therefore, users who use cell phones while driving are at greater risk of being involved. in a traffic accident, mainly older and younger drivers, the latter being those who are subject to greater exposure and high risks in the face of this distraction.